Expatriate spouse adjustment: A study on challenges faced by Asian female expatriate spouses in Finland - Gunasekera, Sasini (2024)
This study examines the personal, interpersonal and environmental adjustment challenges faced by Asian female expatriate spouses relocating to Finland. With globalization extolling the movement of skilled workers across borders, expatriate families, too, experience challenges rarely spoken of, especially by accompanying spouses. This research uses Shaffer and Harrison’s (2001) Expatriate Spouse Adjustment Model to examine in depth the contemporary stages of adjustment, personal, interaction and cultural, and to determine how these dimensions contribute to the final adjustment equation. Focusing particularly on Asian expatriate spouses, who have been largely overlooked in extant expatriate adjustment literature, the study fills a research gap by investigating the cultural and emotional challenges they face when attempting to adjust to the life in a Finnish society which is a far cry from their own. A qualitative research approach was used, and ten Asian female expatriate spouses participated in semi structured interviews. The results show that emotional isolation, homesickness and the harsh climate of northern Finland, where there are long winters, have a big impact on the personal adjustment and are particularly difficult to cope with during the long northern night. Finally, the Interaction adjustment dimension shows us how Finnish society is reserved and that the creation of 'expatriate bubbles' where expatriates socialize with other expatriates prevents them from integrating into the local community. Social interaction and cultural immersion were also severely impeded by language barriers where most people were using English but were unable to communicate with one another because of language barriers. The study demonstrates that participants felt cultural dissonance as the collectivist cultural orientation of their countries of origin was at odds with the individualistic character of Finnish society. Participants experienced emotional difficulties because this did not really mesh with Finnish reality. ...